Intelligenza artificiale, sicurezza nazionale e capitalismo politico. La crisi della riflessività democratica e la necessità di un’etica strategica - De Ruvo, Giuseppe (Filosofia Morale/Moral Philosophy, 2024)
Artificial intelligence, national security and political capitalism. The crisis of democratic reflexivity and the need for strategic ethics Focusing on the U.S. case and drawing on the notion of political capitalism, the article thematizes the relationship between AI governance and the concept of national security, often invoked to protect the American tech ecosystem from China’s technological rise. We will therefore analyze the relationship between national security apparatuses, the market, and public deliberative practices. We argue that the difficulties in implementing AI governance depend not only on the reluctance of Big Tech, but also – and more importantly – on their ties to defense bureaucracies. The article claims that a critical theory of AI cannot be limited to diagnosing and mitigating particular problems emerging from its implementation. Rather, it must deeply thematize the changing relationship between the state and the market, also considering the geopolitical and geoeconomic issues that characterize the political economy of AI. In conclusion, we argue that, for Western countries, taking into account the ethical issues posed by new technologies may also be considered a strategic operation.